Clinical application of functional near-infrared spectroscopy for burn assessment - Kim, Yoo Hwan; Paik, Seung-Ho; Kim, Youngmin; Yoon, Jaechul; Cho, Yong Suk; Kym, Dohern; Hur, Jun; Chun, Wook; Kim, Beop-Min; Kim, Byung-Jo (Frontiers in Bioengineering and Biotechnology, 2023)
Significance: Early assessment of local tissue oxygen saturation is essential for clinicians to determine the burn wound severity. Background: We assessed the burn extent and depth in the skin of the extremities using a custom-built 36-channel functional near-infrared spectroscopy system in patients with burns. Methods: A total of nine patients with burns were analyzed in this study. All second-degree burns were categorized as superficial, intermediate, and deep burns; non-burned skin on the burned side; and healthy skin on the contralateral non-burned side. Hemodynamic tissue signals from functional near-infrared spectroscopy attached to the burn site were measured during fNIRS using a blood pressure cuff. A nerve conduction study was conducted to check for nerve damage. Results: All second-degree burns were categorized into superficial, intermediate, and deep burns; non-burned skin on the burned side and healthy skin on the contralateral non-burned side showed a significant difference distinguishable using functional near-infrared spectroscopy.Hemodynamic measurements using functional near-infrared spectroscopy were more consistent with the diagnosis of burns 1 week later than that of the degree of burns diagnosed visually at the time of admission. Conclusions: Functional near-infrared spectroscopy may help with the early judgment of burn extent and depth by reflecting differences in the oxygen saturation levels in the skin.